A methods engineering study on Phil. Fishing Gears Industries, Inc. - Dato, Czarina T.; Pendel, Vivien I. (Diliman, Quezon City College of Engineering, 2001)
Philippine Fishing Gears Industries, Inc., a subsidiary of Fortune Net and Twine Manufacturing Corporation, in East Canumay, Valenzuela, manufactures fish nets and twines in various sizes for different purposes for the local and international market. The group chose the Annex building where they manufacture small to medium sized fish nets and twines as the focus of the study. In obtaining the standard time in Time Study, the group chose 400/9 twine and fish net production since it is only the product that is manufactured and all its operations are within the building under study. The group used the Streamline Diagnostic Chart for Problem Identification and Cause and Effect (Ishikawa) Diagrams in Problem Analysis. The group also verified the problems. These problems are unavoidable waste, delayed production and poor layout. There are few alternatives generated for each problem identified. To do nothing is the common alternative. In wastage, the alternatives were strict implementation of frequent machine check up and machine overhaul periodically, as well as, purchase of new machines and tight quality control to reduce supply defects. In delayed production, standardizing its manual operations was suggested. Making of material handling equipment is suggested too to remedy the delay in production. In poor layout, placing of floor markings and installing of platforms was suggested. Moreover, it is also suggested to transfer other machines to other building to have a much wider space. Using Cost-Benefit Analysis and Decision Analysis, all the alternatives were evaluated. To reduce the unavoidable waste, there should be strict implementation of machine check-ups and machine overhaul periodically. To decrease the chance of delayed production, manual operations such as twisting, spooling, winding and shuttling should be standardized. Additional material handling equipment should also be made. It would cost P900 per hand truck and can be done in two days. Lastly, there should be floor markings to assign the space for proper temporary storage of materials and equipment. The paint for floor markings would cost P400 for the whole building and will be finished within a day. Moreover, install platforms, these will help to organize the bobbins and in proper handling of bobbins and to ease the workflow. Three platforms will be installed for each twisting machine and would cost P305.00. This will be done within three days from design to install. Time study was also performed on twisting, spooling, winding and shuttling, to come up with a standard time on the mentioned operations. Finally, implementing strategies for each recommendation were presented.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Fisheries; Systems analysis